The Efforts of Teachers in Developing Learning Media for Fiqh at Ira Medan Private MTS - Sari, Delvina; Azhar, Ihsan Satrya (Journal of Educational Sciences, 2025)
This research aims to describe the efforts of teachers in developing learning media for fiqh at MTs Swasta IRA Medan, as well as to identify the obstacles faced and the solutions implemented. The background of this study is based on the importance of learning media in enhancing students' understanding and motivation to learn, especially in the subject of fiqh which contains both theoretical and practical aspects. The research method used is qualitative descriptive, with data collection techniques including observation, interviews, and documentation. The results of the study show that fiqh teachers at MTs Swasta IRA Medan have creatively endeavored to develop varied learning media that align with the characteristics of the material and the needs of students. The media used include images, videos, question cards, and direct practice such as simulating prayer movements and animal sacrifice using simple aids. The challenges faced by teachers include limitations in technological infrastructure, time, budget, and difficulties in aligning media with the content. The solutions implemented include the use of projectors, the use of simple and free media, and the utilization of local resources. The use of media has proven to increase students' motivation to learn and their understanding of fiqh material.